(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-3-146-154 The article raises the question of the folklorism of V.V. Mayakovsky, whose artistic heritage in literary criticism from these positions has been little studied. The latent forms of penetration of the folk tradition into the poetics of the author of the beginning of the 20th century are considered. Folklore in the study is understood comprehensively, culturally and philologically expanded, taking into account the forms of myth, ritual, that is pre-genre formations. The material for the hermeneutic analysis was the poem "An extraordinary adventure that happened with Vladimir Mayakovsky in the summer at the dacha", which is especially distinguished by literary critics in the poet’s work. Much attention is paid to the problem of national topics, the archetype of the World Mountain in the verbal culture of modernism, whose representatives were acutely aware of the problem of feeling space and time, "top" and "bottom", "day" and "night". The folklore commentary on the poem also allows rethinking many issues of the poet’s work from ontological and metaphysical positions. This poem has a great cultural potential for the study of solar images in the Russian poetry of the Silver Age, artistic anthropocosmism, which was associated with the philosophy of cosmism. The results of the work can also be used in teaching courses on Russian literature of the XX century, folklore, philosophy. Key words: creativity of V. V. Mayakovsky, folklore tradition, archetype, Russian fairy tale, futurism, Georgian folklore